Peranakan Chinese Identities in Globalizing Malay Archipelago, by Leo Suryadinata. Singapore: ISEAS Publishing, 2022. v + 289 pp. ISBN 978-981- 4951-67-8. (KEMANUSIAAN The Asian Journal of Humanities, 2025)
The author wants to illustrate the complexities of Peranakan identities, which Leo Suryadinata admits are not homogeneous and that “the identity of the Peranakan Chinese is far from clear” (p. 45). Yet with his most recent book, Peranakan Chinese Identities in the Globalizing Malay Archipelago, Suryadinata, a retired sinologist in Singapore who has written extensively on the Chinese in Indonesia, attempts to explore Peranakan identities mainly in Indonesia, Malaysia and Singapore (IMS).